2016
DOI: 10.18203/issn.2454-5929.ijohns20161595
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the medical and surgical management of chronic rhinosinusitis with polyposis

Abstract: Background: Chronic rhinosinusitis (CRS) is a group of disorders characterized by inflammation of the mucosa of the nose and paranasal sinuses of at least 12 consecutive weeks duration. Surgical intervention may be required if severe symptoms of obstruction and infection prove medical treatment to be ineffective. Little is known about the outcomes of patients electing to continue medical management or the comparative effectiveness of continued medical therapy with FESS. Methods: The study was conducted on 126 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Similarly, the study undertaken by Modgil also showed that patients who underwent only medical treatment and those who underwent combined medical and surgical treatments showed equal amounts of improvements. 8 Khalil et al in their review of large randomized control…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the study undertaken by Modgil also showed that patients who underwent only medical treatment and those who underwent combined medical and surgical treatments showed equal amounts of improvements. 8 Khalil et al in their review of large randomized control…”
Section: Discussionmentioning
confidence: 99%